Immunotherapy in melanoma. (27th August 2018) - Mitchell, Tara C; Feld, Emily
Immunotherapy has dramatically improved the prognosis for patients with melanoma and has become the cornerstone of treatment for those with advanced disease. The role of immunotherapy continues to expand with multiple new agents approved in the adjuvant as well as metastatic setting, as first-line therapy and beyond. We review the currently approved drugs for the treatment of melanoma, along with clinical trial data, adverse side effects, response assessment and future directions.